Careers Making Committees Work. - Selinger, C. (IEEE spectrum)
This paper presents some ways of improving the effectiveness and satisfaction of working on a committee. In a properly run committee, you have the opportunity to learn management skills and make contacts that can boost your career, and get something done as well